Implementation of Financial Aid for Local Political Parties in Banda Aceh City - Al Fathir, Muhammad Alif; Hasba, Irham Bashori (Jurnal Ius Constituendum, 2024)
This study examined the allocation of financial aid funds from the Banda Aceh Regional Government Budget (APBK) to Local Political Parties X and Y in Banda Aceh. This study conducted empirical juridical research and presented the findings of field research using two analytical frameworks: Legal Effectiveness theory and Siyasah Maliyah Fiqh theory. It focused on local political parties since they represent a unique kind of democracy in the Aceh region. From the standpoint of legal effectiveness theory, the findings of this study suggest that the supporting facilities in the form of financial aid and legal factors are adequate and suitable. Nevertheless, barriers remain present within law enforcement, society, and culture. From the accumulated results of the components of the theory of legal effectiveness, a fiqh siyasah maliyah perspective is obtained. Thus, it can be concluded that the principles of ownership and management are still hampered by transparency, accountability, and openness of information to the community. The principle of abuse and corruption is already working well, but the accuracy of targeting financial funds must be improved The people's benefit has not been completely realized as a result of the aid use not being targeted.. The principle of amar ma'ruf nahyi mungkar has also not been fully implemented because it is hampered by a crisis of public trust, the party's understanding of regulations, and the infrastructure supporting transparency and accountability.